Malignant melanoma: statiscal analysis - Borges, Freddy (Cirugía del Uruguay, 1974)
A study was made of 123 cases of malignant melanoma which were treated at the "Hospital de Clínicas" from 1953 to 1973. The incidence and origin of ali patients in analyzed. Distribution by sex, ectary histogram, locus and clínical state at first visit. By comparison there arises coincidence with other statistics. Mention was made of the high incidence of patients in advanced and very advanced stages of the disease at the time of the· first visit to the doctor.